2020
DOI: 10.1007/s12178-020-09654-8
|View full text |Cite
|
Sign up to set email alerts
|

Periprosthetic Fractures in Reverse Total Shoulder Arthroplasty: Current Concepts and Advances in Management

Abstract: Purpose of Review Expanded indications for reverse total shoulder arthroplasty (RSA) have raised awareness of associated complications, including periprosthetic fractures. The purpose of this article was to provide a comprehensive update on how, when, and why RSA-related periprosthetic fractures occur, as well as to describe the current treatment strategies. Recent Findings Periprosthetic acromial and scapular spine fractures occur in up to 4.3% of cases and periprosthetic humeral fractures occur in approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 56 publications
1
17
2
1
Order By: Relevance
“…We observed a total of 469 periprosthetic fractures, representing a rate of 3.4%, lower than the 7.8% rate reported by Brusalis et al 159 Moreover, we observed a higher rate of postoperative fractures compared to intraoperative ones, while other Authors reported the opposite. 13,158…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…We observed a total of 469 periprosthetic fractures, representing a rate of 3.4%, lower than the 7.8% rate reported by Brusalis et al 159 Moreover, we observed a higher rate of postoperative fractures compared to intraoperative ones, while other Authors reported the opposite. 13,158…”
Section: Discussioncontrasting
confidence: 86%
“…In our analysis, the overall complication rate was 12.2%, which is much lower than the 68.5% reported by Zumstein et al, 9 but closer to the 15% and 16.1% reported by other Authors. 158,159 Dislocation was the most common complication observed with a rate of 2.5%, lower than the 1 reported by Bohsali et al (5%) and Zumstein et al (4.7%). 9,158…”
Section: Discussioncontrasting
confidence: 54%
“… 30 Others believe that the design of the prosthesis with a different centre of rotation plays a role. 31 Nyffeler et al question the theory of an increased tension in the deltoid or a stress fracture in their recent study. The authors discuss the altered shape of the shoulder after implantation of an RSA with a greater exposition of the acromion and the scapular spine, which makes it more vulnerable to direct trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, fractures occur frequently during arm positioning, such as extension, rotation, and translation, to dislocate or reduce the humeral head. During arm positioning, spiral fracture of the humeral metaphysis or greater tuberosity avulsion fracture could occur [ 47 ]. Other risk factors for intraoperative humeral fracture are osteopenia, rheumatoid arthritis, and revision surgery [ 47 ].…”
Section: Intraoperative Fracturementioning
confidence: 99%
“…During arm positioning, spiral fracture of the humeral metaphysis or greater tuberosity avulsion fracture could occur [ 47 ]. Other risk factors for intraoperative humeral fracture are osteopenia, rheumatoid arthritis, and revision surgery [ 47 ]. To prevent intraoperative humeral fractures, surgeons should be aware of the risk factors for periprosthetic fracture [ 48 ].…”
Section: Intraoperative Fracturementioning
confidence: 99%